The Office of Management and Budget and the presidency, 1921-1979 - Berman, Larry, 1951- (Princeton legacy library., 1979)
In the first comprehensive study of the Office of Management and Budget Larry Berman traces its evolution from a once impartial and objective presidential staff agency to The Office of Meddling and Bumbling (TOMB), as it was known by the end of the Nixon administration. In doing so he analyzes both its established role and the subsequent changes in this role as different presidents attempted to respond to a variety of external demands. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books f.